A graduate recital in wind band conducting: Serenade in D Minor Op. 44, Antonin Dvor̆ák and Symphony no. 6 (Symphony for band), Vincent Persichetti - Hardy, Meghan C. (Kansas State University, 2009)
This document was submitted to the Graduate School of Kansas State University as a partial requirement for the Master’s in Music Degree. This document includes the historical, theoretical, performance, and rehearsal consideration of the works performed in the corresponding graduate recital. These works are Antonin Dvořák’s Serenade in D Minor, Op. 44 and Vincent Persichetti’s Symphony Number Six for Band. The analysis format for this report is based on the Blocker/Miles Unit Study technique found in the Teaching Music through Performance in Band series, as well as the Tracz concept of macro-micro score analysis. The performances of the Kansas State University Symphony Band and a chamber ensemble which consisted of faculty and Symphony Band members served as the basis for the technical, musical, and stylistic evaluations and analysis.
Keywords: Dvorak; Persichetti; Wind band; Conducting; Serenade; Symphony; Music (0413)